Akad Syirkah dalam fikih muamalat : Konsep, Prinsip, dan Implementasi dalam Ekonomi islam di kKoperasi STAI As-Sunnah Deli Serdang: Akad Syirkah dalam fikih muamalat : Konsep, Prinsip, dan Implementasi dalam Ekonomi islam di Koperasi STAI As-Sunnah Deli Serdang - Dina Marni; Andini, Ghina; Agustin; Tri Hidayatullah; Ahmad Nizar (SALSABIL : Jurnal Syariah dan Hukum Ekonomi, 2025)
This research examines the application of the syirkah contract in the profit-sharing system implemented at the As-Sunnah Islamic Religious College (STAI) Medan, which adopts the cooperative concept. As we know, conventional cooperatives today often contain practices of riba and gharar, which have been strictly prohibited by Allah ﷻ in the Quran and the hadith of the Prophet ﷺ. This research aims to analyze the implementation of the syirkah contract within the structure of the STAI As-Sunnah cooperative and ensure its compliance with the principles of Islamic economic law. The approach used in this research is a qualitative approach with field research methods. (field research). Data were collected through interviews and direct observations of the parties involved in the STAI As-Sunnah cooperative. The research results show that the application of the syirkah contract in the STAI As-Sunnah cooperative includes the management of cooperative collaboration and its relevance to the principles of Islamic economic law governing the cooperative. This research provides a clear picture of the syirkah contract law and its implementation in the STAI As-Sunnah cooperative. From this research, it can be concluded that the syirkah contract has two forms, namely syirkah of ownership (like inheritance) and syirkah of contract, which consists of several types, namely syirkah mufawadhah, maal/'inan, abdan, wujuh, and mudharabah.